Analisis Panjang Antrian Kendaraan pada Persimpangan Baddoka (Studi Kasus : Jalan Perintis Kemerdekaan KM 17) - Rais Rachman; Feri Famara; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2023)
An intersection is a meeting place where two or more roads join together to intersect. Calculations and analysis use the method of calculation in the 2014 Indonesian Road Capacity Guidelines (PKJI). This four-signal intersection has four arms where the north-facing approach on Jl. Makassar – Maros axis consisting of 4 lanes with a road width of 15 meters. on the east west approach Jl. Dg. This Ramang has 2 lanes and a road width of 7.5 meters, on the approach to the west of Jl. Batara Bira baddoka has 2 lanes and a road width of 6.5 meters. Based on the results of data analysis regarding the length of vehicle queues, during peak hours in the morning the north arm has the largest queue length of 112.58 m, during peak hours in the afternoon the south arm the queue length the largest is 76.93 m, and at peak hour in the afternoon of the south arm the largest queue length is 344.68 m. Based on the results of analysis of research data regarding the average delay that occurs at the intersection with the Baddoka signal, the largest average delay value that occurs during the morning peak hours of the northern arm is 285.36 seconds/cur, during the afternoon peak hours of the southern arm is 250.59 sec/cur, and during the afternoon peak hours of the south arm the highest average delay value is 808.24 sec/cur.